2011
DOI: 10.1159/000335331
|View full text |Cite
|
Sign up to set email alerts
|

Trends and Novel Approaches in Neoadjuvant Treatment of Breast Cancer

Abstract: Breast cancer is the most prevalent malignant disease in women worldwide. Traditionally, surgical tumour resection was the primary step within the treatment algorithm of early stage disease; systemic therapy in order to reduce the rate of systemic recurrences followed. National Surgical Adjuvant Breast and Bowel Project (NSABP) trial B-18 found that pre- and postoperative administration of chemotherapy was equally effective. This study therefore established neoadjuvant chemotherapy as a valid treatment option,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Multimodal therapy, including chemotherapy, surgery, and radiation, is the treatment of choice that has shown the highest percentage survival in such patients with breast cancer. 4,5 Particularly, chemotherapeutic schemes based on anthracycline and taxanes are widely accepted as first alternatives in the treatment of breast cancer [6][7][8] ; these therapeutic strategies provide a benefit in recurrence-free survival as well as overall survival. 9,10 Management in clinical practice, using a neoadjuvant chemotherapy regimen in either a concomitant or sequential manner, is preferred in locally advanced breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Multimodal therapy, including chemotherapy, surgery, and radiation, is the treatment of choice that has shown the highest percentage survival in such patients with breast cancer. 4,5 Particularly, chemotherapeutic schemes based on anthracycline and taxanes are widely accepted as first alternatives in the treatment of breast cancer [6][7][8] ; these therapeutic strategies provide a benefit in recurrence-free survival as well as overall survival. 9,10 Management in clinical practice, using a neoadjuvant chemotherapy regimen in either a concomitant or sequential manner, is preferred in locally advanced breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Although today the sequential administration of these agents is usually preferred, ABCSG trials 14 and 24 identified 6 cycles of concomitant ED (with or without capecitabine) as a potential neoadjuvant treatment standard. 12,13 Accordingly, in the present study, standardized NACT consisted of 6 cycles of ED administered intravenously once every 3 weeks (E 75 mg/m 2 and D 75 mg/m 2 ) with primary granulocyte colony-stimulating factor support.…”
Section: Preoperative Systemic Treatmentmentioning
confidence: 99%